THE ESTIMATION OF THE RELIABILITY OF THE DATA FROM THE SHAMAKHA SPECTROPHOTOMETRIC CATALOGUE - V. M. Tereschenko (Academic Scientific Journal of Computer Science, 2019)
On the basis of existing spectrophotometric catalogues and individual articles we plan to create a joint uniform catalogue of stars with known distributions of energy in their spectra. As original catalogues we intend to use catalogues which were created in the Fesenkov astrophysical institute, Sternberg astronomical institute, Main astronomical observatory RAS, Odessa astronomical and Shamakha astrophysical observatories. At the preliminary stage of the proposed project, it is necessary to assess the reliability of the data of initial catalogues. The first three catalogues are already investigated in this respect. In this paper, we analyze the data of the Shamakha catalogue. The reliability of the data is estimated by indirect means – according to the similarity of magnitudes calculated from the energy distribution with the directly observed star magnitudes using the most accurate photometric WBVR-system. Calculations of the magnitudes and color-indexes are made using standard formulas for synthetic photometry. Then, the difference (residuals) between calculated and directly observed stellar magnitudes was computed. The results of calculations are presented in the table. On their basis the dependencies of residuals from the V- magnitudes and color-indexes were plotted. From them follows that noticeable systematic errors in Shamakha spectrophotometric catalogue are absent. However, there are a significant number of accidental residuals reaching 0.20m and higher. The results of the calculations will be used for creating joint catalogue and for the selection of standard stars from it.